Three theoretical approaches to play therapy 11th Annual APT International Conference, October 15, 1994 - Association For Play Therapy, Inc.; APT International Conference 1994) ([California] : Association For Play Therapy, Inc., 1994)
A conference which presents by Drs. John Allan, Louise Guerney and Kevin O'Connor that talk on three different theoretical approaches to play therapy and what the different between each approaches
Title from container
Presenter: Drs. John Allan, Louise Guerney, Kevin O'Connor
Keywords: Play therapy; Cognitive therapy; Cognitive therapy for children